(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
The aim of this study was to evaluate the relationship between components of metabolic syndrome (MetS)—abdominal obesity, dyslipidaemia and impaired glucose metabolism—and left ventricular diastolic dysfunction (LVDD) in hypertensive patients. A cross-sectional sample of 190 adults with confirmed arterial hypertension, followed at a cardiology department in the Bukhara region between 2024 and 2025, was analysed. MetS was diagnosed according to International Diabetes Federation criteria using waist circumference, triglycerides, high-density lipoprotein cholesterol, blood pressure and fasting plasma glucose. Echocardiography was performed to assess LV diastolic function based on transmitral E/A ratio, E/e’ index and left atrial size, and LVDD was graded from I to III.MetS was present in 60% of patients; in this group, both the prevalence and severity of LVDD were higher than in those without MetS (78% vs. 49%). The mean E/e’ value increased stepwise with the number of MetS components (10.2±2.1 in patients with fewer than three components, 12.8±2.4 in those with three to four components and 15.1±2.9 in those with all five components). Positive correlations were observed between waist circumference, triglyceride levels and LVDD grade. These findings suggest that active identification and targeted treatment of MetS components in hypertensive patients are important for preserving LV diastolic function and slowing progression toward overt heart failure.